ANALISIS PENYUSUNAN ANGGARAN PADA CV. BUANA RAYA MEDAN - ARWIN .; WILLIAM LIUS; SISKA MEDIYANTI; RINA FRISKA BR SIAHAAN; TASIK UTAMA (JURNAL ILMIAH SIMANTEK, 2019)
A budget is a periodic financial plan that covers a company's operational activities within a certain period. Budgeting is theprocess of operating a plan in the form of qualifications, which are usually in monetary form, for a certain period of time. Witha good budget, the company can arrange planning the amount of income desired from the results of its business, the amountof expenses, and profits to be achieved in a period. The formulation of the problem in this study is "How is the budgetpreparation at CV. Buana Raya Medan? The purpose of this study is to analyze the preparation of the budget at CV. BuanaRaya Medan. The research method used in this study is a qualitative research method. Data sources used include primarydata and secondary data. Data collection techniques used were interviews and documentation. In this study, researchersused source triangulation. From the results of the analysis of the preparation of the budget on the CV. Buana Raya Medan isknown that in 2012, the company's profit exceeded the target, where the company targeted a profit of Rp. 777,003,156, whilethe company's profit of Rp. 783,212,617. In 2013, the company's profit also exceeded the target, where the companytargeted a profit of Rp. 791,415,915, while the company's profit of Rp. 806,845,903. In 2014, the company's profit was lowerthan the target, where the company targeted a profit of Rp. 1,740,107,783, while the company's profit is only Rp.1,625,985,169. Thus, the preparation of the budget has not been done well on the CV. Buana Raya Medan.